Open and Closed Knowledge Systems, the 4 Stages of Cognition, and the Cultural Management of Birth - Davis-Floyd, Robbie E. (Frontiers in Sociology, 2018)
This conceptual article looks at levels or Stages of Cognition, equating each of the four stages I examine with an anthropological concept. I equate Stage One--rigid or concrete thinking--with Naïve Realism ("our way is the only way", Fundamentalism ("our way should be the only way and those who do not follow it are doomed"), and Fanaticism ("our way is so right that everyone who disagrees with it should be either converted or eliminated"). I equate Stage Two with ethnocentrism ("there are lots of other ways out there, but our way is best"). The next two Stages represent more fluid types of thinking--I equate Stage Three with cultural relativism ("all ways are equal in value and validity"), and Stage Four with global humanism ("there must be higher, better ways that can support cultural integrity while also supporting the individual rights of each human being"). I then categorize various types of birth practitioners within these Four Stages, while showing how ongoing stress can cause even the most fluid of thinkers to shut down cognitively and operate at a Stage One level that can involve obstetric violence--an example of further degeneration into Substage--a condition of burnout or "losing it." I show how ritual can help practitioners ground themselves at least at a Stage One level and offer ways in which they can rejuvenate and re-inspire themselves. I also describe a few of the ongoing battles between fundamentalists and global humanists and the persecution globally humanistic birth practitioners often experience from fundamentalist or fanatical Stage One practitioners and officials, often referred to as the "global witch hunt."